Emotion recognition with multiple physiological parameters based on ensemble learning - Yilong Liao; Yuan Gao; Fang Wang; Li Zhang; Zhenrong Xu; Yifan Wu (Scientific Reports)
Abstract Emotion recognition is a key research area in artificial intelligence, playing a critical role in enhancing human-computer interaction and optimizing user experience design. This study explores the application and effectiveness of ensemble learning methods for emotion recognition based on multiple physiological parameters. A dataset was systematically constructed by preprocessing data from electroencephalogram (EEG), galvanic skin response (GSR), skin temperature (ST), and heart rate (HR) collected from 38 subjects while watching short videos. We proposed a hybrid model framework combining Convolutional Neural Networks (CNN) and Long Short-Term Memory (LSTM) networks, trained and optimized using a random seed initialization strategy and a cosine annealing warm restart strategy. To further enhance performance, various strategies were designed and evaluated. The results showed that applying advanced preprocessing techniques significantly improved data quality, while the hybrid model effectively leveraged the advantages of both CNN and LSTM. Incorporating the cosine annealing warm restart strategy further boosted model performance. Using a soft voting ensemble method, the proposed approach achieved a 96.21% accuracy rate in classifying seven emotions—calm, happy, disgust, surprise, anger, sad, and fear, indicating its ability to accurately capture emotional responses to short videos. This study presents an innovative approach to emotion recognition using multiple physiological parameters, demonstrating the potential of ensemble learning for complex tasks. It offers valuable insights for the development of effective applications.